2022
DOI: 10.3102/0013189x221109178
|View full text |Cite
|
Sign up to set email alerts
|

Test Score Patterns Across Three COVID-19-Impacted School Years

Abstract: The COVID-19 pandemic has been a seismic and ongoing disruption to K–12 schooling. Using test scores from 5.4 million U.S. students in Grades 3–8, we tracked changes in math and reading achievement across the first 2 years of the pandemic. Average math test scores in the fall of 2021 in Grades 3–8 were .20–.27 standard deviation (SD) lower relative to same-grade peers in the fall of 2019, while reading test scores decreased by .09–.18 SD. Achievement gaps between students in low-poverty and high-poverty elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 8 publications
3
64
2
1
Order By: Relevance
“…1) how much progress did bilingual and monolingual children make in their English language and literacy development during the COVID-19 school disruption? As most COVID-19 related studies showed slower learning gains (e.g., Kilbride et al, 2021aKilbride et al, , 2021bKuhfeld et al, 2022), we predicted that across groups, children may show slower-than-expected progress in comparison to prior age-related norms. In particular, bilingual children were expected to be especially susceptible to having slower learning gains in both spoken and written English language skills.…”
Section: The Present Studymentioning
confidence: 82%
See 1 more Smart Citation
“…1) how much progress did bilingual and monolingual children make in their English language and literacy development during the COVID-19 school disruption? As most COVID-19 related studies showed slower learning gains (e.g., Kilbride et al, 2021aKilbride et al, , 2021bKuhfeld et al, 2022), we predicted that across groups, children may show slower-than-expected progress in comparison to prior age-related norms. In particular, bilingual children were expected to be especially susceptible to having slower learning gains in both spoken and written English language skills.…”
Section: The Present Studymentioning
confidence: 82%
“…Georgiou (2021) found that, while English-speaking Canadian 2nd and 3rd graders had decreases in their reading fluency and comprehension skills, 4th-9th graders maintained adequate reading progress compared to the cohorts in pre-pandemic years. Kuhfeld et al (2022) analyzed reading achievement data on 5 million US students and found that 3rd-8th graders had no significant change in their reading performance by the 2020 fall semester (i.e., the first semester after the major school disruption).…”
Section: Impacts Of Covid-19 On Language and Reading Development Amon...mentioning
confidence: 99%
“…Prior to the pandemic, Black children were more likely to lose instructional time due to disproportionate discipline strategies (Losen & Martinez, 2020; U.S. GAO, 2018), and evidence suggests prepandemic losses were magnified by pandemic‐related school closures (Kuhfeld et al, 2022). Institutionalized patterns of racial discrimination against Black children, including disparate disciplinary practices resulting in the school‐to‐prison pipeline (C. Y. Kim et al, 2010), have fueled deep distrust of schools among Black communities (Gilbert et al, 2020; Shapiro et al, 2021).…”
Section: Consequences Of Covid‐19 At the School Levelmentioning
confidence: 99%
“…Poor school conditions existed long before the pandemic (Frankenberg et al, 2019) exacerbation of inequalities brought on by the pandemic is particularly troubling for Black families in under-resourced schools. For example, in the early months of the pandemic, scholars forecasted that low-SES schools would see greater learning losses among their students as a function of school closures , and follow-up studies show evidence of these disparities (Agostinelli et al, 2022;Kuhfeld et al, 2022). Beyond academic learning, pandemic closures and subsequent reopening restrictions have required schools to invest resources to support student and staff′s physical safety, mental health, and socioemotional well-being.…”
Section: Consequences Of Covid-19 At the School Levelmentioning
confidence: 99%
“…Moreover, there is also a growing literature on the underpreparedness of students entering college after two years of remote or otherwise disrupted learning (Kuhfeld et al, 2022 ). Jack et al (forthcoming), looking at district-level schooling data in the United States for grades 3–8 found significantly larger declines in math and English language arts pass rates in districts forced to provide remote learning compared to those that were allowed to remain in-person.…”
Section: Wrong Curves Wrong Policymentioning
confidence: 99%